2003
DOI: 10.1046/j.1365-2133.2003.05352.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle differences in twin pairs discordant for basal cell carcinoma of the skin

Abstract: The results suggest a role for smoking and possibly also for other lifestyle factors in the risk of contracting BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 24 publications
5
110
3
Order By: Relevance
“…Therefore, high solar UVB radiation levels imply a great capability to synthesize vitamin D in the northern regions of Chile. A recent analysis determined that the diagnosis of NMSC was associated with a reduced risk of several vitamin D-sensitive cancers (30,31). This was in accordance with low solar UVB radiation levels in the southern cities of Chile in winter.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, high solar UVB radiation levels imply a great capability to synthesize vitamin D in the northern regions of Chile. A recent analysis determined that the diagnosis of NMSC was associated with a reduced risk of several vitamin D-sensitive cancers (30,31). This was in accordance with low solar UVB radiation levels in the southern cities of Chile in winter.…”
Section: Discussionmentioning
confidence: 59%
“…Still, a limited number of epidemiological studies investigated its etiological factors. Sunlight exposure and a history of sunburns contribute to a large proportion of BCC in white populations, but several other factors have been suggested [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Prior to the approval of TCIs we preformed a case-control study which demonstrated that the odds ratio (OR) of association of NMSC in patients with AD was either the same or slightly less than in those with other inflammatory dermatologic illnesses [11]. A study of twins also showed that the development of basal cell carcinoma was not associated with AD [12]. However, a recent study from Sweden indicated that patients hospitalized for AD had a trend, which was not statistically significant, toward a 50% increase in skin cancers about 15 years later in life [13].…”
Section: Introductionmentioning
confidence: 99%